Diet overlap and potential competition between North Island brown kiwi chicks (Apteryx mantelli) and ship rats (Rattus rattus) for limited resources on Ponui Island, New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Ecology at Massey University - Shapiro, Lee Mark (Massey University, 2005)
The introduction of mammals to New Zealand has devastated the native avifauna. Although not the most severely affected native bird species, all five species of kiwi (Apteryx Spp.) have sustained a severe loss of numbers and range. Kiwi have declined on the mainland from a failure to replace their numbers due to a high mortality rate of kiwi chicks. The main reason for this mortality is predation by introduced stoats (Mustela erminea). Many kiwi mainland populations have predator control enabling the recruitment of chicks. However a consequence of predator removal can be an explosion of rodent populations at control sites. Rodents do not directly prey on kiwi chicks but prey on invertebrates and these rodent population explosions may affect the number of invertebrates available to other forest dwelling animals such as kiwi. The potential exists for competition between rats and kiwi chicks as both feed on soil surface and leaf-litter invertebrates. Evidence from Kapiti Island where kiwi chick recruitment was high following rat eradication supports the competition hypothesis. The aim of the current study was to investigate the diet overlap and thus establish whether there was potential for competition for food between rats and kiwi chicks on Ponui Island in Auckland's Hauraki Gulf. Ponui Island is an ideal location for this research because there is a rat population and a high density of North Island brown kiwi, but no stoats. Kiwi chicks were measured and weighed weekly to determine growth rates, transmitters were changed every second week. Kiwi chick faecal samples were collected weekly from radio tagged individuals and the contents compared to those from ship rat stomachs, and the invertebrates available. Kiwi chicks and ship rats overlapped in the surface dwelling invertebrate component of their diets. Pitfall traps revealed no overall difference in the number and type of invertebrates found in bush and scrub habitat but weta and spiders were more abundant in scrub than bush, this was also the preferred kiwi chick habitat and was reflected in their diet. The only rats caught in Ponui forest habitat were ship rats (Rattus rattus) and their diet was established from monthly kill trapping and by examining the contents of their stomachs. Ship rats ate mostly surface and litter dwelling invertebrates of the orders Coleoptera, Orthoptera and of the class Chilopoda. The prey they consumed closely followed environmental abundance and availability of invertebrate species. The density of ship rats was estimated by carrying out a mark-recapture experiment over three months. Ship rat densities were found to be higher than most mainland ship rat density studies previously carried out in New Zealand. But the estimated density of ship rats on Ponui was similar to estimates undertaken for ship and Norway rats (Rattus norvegicus) on several New Zealand offshore islands including Campbell, Motutapere and Tawhitinui Island. The environmental abundance of invertebrates was measured with the monthly collection of pitfall traps and soil core samples in bush, scrub and farmland habitat and leaf-litter samples in bush and scrub habitat where kiwi chicks and ship rats were monitored. There was no overall difference in the number and taxa of invertebrates found in scrub and bush habitat, however there were several individual taxa differences. There were significantly higher numbers of weta and spiders caught in pitfall traps in scrub compared to bush habitat over winter, spring and summer months. Recce plots were used to describe the vegetation composition in bush and scrub habitat across the study site and assess any impact this may have had on the make up and numbers of invertebrate taxa in those different habitats. Scrub and bush habitat differed in the plant species composition, average canopy height and percentage of leaf-litter ground cover. Although this did not have a significant effect on the overall invertebrate fauna of the two habitat types there were significant differences in the numbers of several key surface and soil dwelling invertebrate prey taxa. Kiwi chicks on Ponui Island showed little growth over the four months they were monitored; the severity of their lack of sustained growth was illustrated when compared to the growth of chicks from the Warrenheip Operation Nest Egg crèche. Of the eight kiwi chicks that hatched from the monitored population on Ponui Island only one survived more than six months. There are several possible reasons for the lack of chick development; these include kiwi chick competition for invertebrate prey with ship rats, other kiwi chicks and adult kiwi and also low invertebrate prey availability and abundance.
Keywords: New Zealand -- Ponui Island; Ponui Island (N.Z.); North Island brown kiwi; Rattus rattus; Black rat